An insider perspective on community gains: A subjective account of a Namibian rural communities׳ perception of a long-term participatory design project. Issue 74 (February 2015) - Kapuire, Gereon Koch; Winschiers-Theophilus, Heike; Blake, Edwin
Abstract: Community-based co-design takes place within a communal value system and opens up a new debate around the principles of participation and its benefits within HCI4D and ICTD projects. This study contributes to a current gap of expression of participants׳ gains, especially from an indigenous and marginalized rural communities׳ perspective. We have collected community viewpoints concurrently over the past five years of our longitudinal research project in rural Namibia. A number of themes have emerged out of the data as extracted by our native researcher, such as the special importance of learning technology, appreciation of the common project goal, the intrinsic pleasure of participation, frustrations about exclusions and other concerns, as well as immediate rewards and expectations of gaining resources. We acknowledge our own bias in the curation of viewpoints, and incompleteness of subjectivities while embedding our discussion within a local contextual interpretation. Through our learning from the communities we argue for a shift in perspective that acknowledges local epistemologies in HCI and participatory design and research. We suggest considering harmony and humanness as the primary values guiding community-based interactions. We discuss several challenges in the collaboration and co-creation of new knowledge at the frontier of multiple cultural, linguist, research and design paradigms. In the absence of generalized guidelines we suggest to pursue local workability while producing trans-contextual credibility. Highlights: Subjective viewpoints of participants in participatory design project. Local rural researcher׳s reflection and data collection presented. Importance of learning, project aim alignment and intrinsic pleasure in participation. Frustrations about exclusions, project continuity and resource scarcity. Self-consciousness and pride as main impact of participation.